“Estudio de un sistema solar fotovoltaico residencial conectado a la red para el sector de Saquisilí con la normativa del ARCONEL 003/18” - Otacoma Cusicahua, William David (2021)
The purpose of this research is to supply electricity to homes located in Saquisilí Canton BY solar energy. The photovoltaic solar system interconnected to the grid is a type of installation in which three elements intervene: solar panels, energy inverter and the electric line of the grid, as well as the dimensioning and design of the photovoltaic system taking into account Arconel 003/18 regulations. For the project design, radiation data from the Meteonorm source was used, which allowed us to carry out a radiation projection for the year 2020, having a daily average of 5.69 kWh / (m2 * day). The daily demand of the home was estimated with the Fluke 435 series II analyzer, which registered an average daily power between the hours of 6:00 am to 6:00 pm of 2 238.25 W and a power consumption of 1 2181, 22 Wh. he photovoltaic system has nine solar panels, whose installed capacity is 3 kW, respectively located on the roof of the house in a free area of 63.8 m2. In this way, the system will be able to deliver 4,639.57 kWha to the home annually and avoid the emission of 2.81 tons of CO2 per year. To finish the financial project study, it has an investment of 3,995.28 USD, where two economic scenarios were considered: in the first one (optimal) there is no variation in the economic parameters, while in the second one (pessimistic), all these economic parameters are taken into account.